Suppression of ozone formation at high temperature in China: from historical observations to future projections - Ning, Guicai (2023)
Ozone suppression (OS) – negative correlation between ozone (O3) and temperature above a cutoff temperature (Tx) – has yet to be fully understood, causing large uncertainties in future global O3 projection. Given China's serious air pollution and large population, its future O3 projection has important implications on global population health. The level of OS in China under climate change needs to be better understood. We assess OS in China and develop hybrid models with OS to project future O3 using downscaled climate projections. In 2015–2019, ∼19% of cities in China show OS, of which 80% has Tx > 34°C. Moreover, O3 is projected to suppress more and up to 11.75% of future regional O3 in high-emission scenarios in the late 21st century. Our findings highlight the essentiality to incorporate OS into chemical transport models for more accurate future O3 projection.